Phosphorus recovery from anaerobic membrane bioreactor (AnMBR) permeate by chemical coagulation and bioelectrochemical processes - Heronemus, Evan (Kansas State University, 2021)
As the world’s population continues to increase, demand for natural resources will continue to grow, especially those needed for the production of food, energy, and water. Dwindling resources have already began pushing society towards a circular economy model, as supply chain disruptions and price instability of these limited resources creates a need to generate more raw materials from waste products. Phosphorus is one of these critical raw materials being depleted, which is mined for approximately 20 million tons each year. It is unclear how long these phosphate reserves will last, but it is estimated that demand could outpace supply this century, possibly by 2035. Anaerobic membrane bioreactors (AnMBRs) represent an emerging environmental biotechnology platform with the potential to simultaneously recover water, energy, as well as nutrients from a variety of different concentrated wastewaters, recycling the waste as raw materials into the circular economy. While AnMBRs keep the nutrients in a more easily recoverable form in the liquid stream, there is limited work demonstrating nutrient recovery paired with an AnMBR. This study focused on capturing the phosphorus present in the permeate from the AnMBR using conventional chemical coagulation-flocculation-sedimentation processes, further aided by emerging platforms such as bioelectrochemical systems for further polishing of the effluent and enhancing the nutrient product quality. This research was accomplished through four objectives. Objective 1 sought to evaluate performance of coagulation-flocculation-sedimentation systems for the simultaneous removal of phosphorus and sulfide from wastewater permeate after treatment through an anaerobic membrane bioreactor (AnMBR). Iron addition was found to effectively remove phosphate at an efficiency of over 90% in municipal wastewater with a sulfide removal of over 99% when the system was continuously operated, the findings from which were published in a peer reviewed journal. Calcium addition showed high phosphate removal with no significant sulfide removal, but long-term continuous pilot scale data is still pending future work. Objective 2 aimed to assess the efficiency of iron phosphate recovery form wastewater and its potential as a fertilizer, and it was found that the recovered nutrient product acted as a phosphorus sink, giving it certain applications, but making it an ineffective fertilizer product. These findings were also published in a peer review journal. Objective 3 focused on tailored chemical addition of calcium to form the most calcium phosphate product that is most plant available. pH control was found to be important for producing a better product. Further removal will still be required after coagulation to meet discharge standards for swine wastewater, and capacitive deionization has the potential to achieve this, but future work outside the scope of this thesis is needed. However objective 4 aimed to provide preliminary steps for this process, by comparing the Coulombic recovery from acetate-fed and glucose-fed microbial electrochemical systems to determine the feasibility of directly feeding wastewater for capacitive deionization of phosphate. These experiments found methane to be a substantial electron sink at the anode, limiting the Coulombic efficiency of reactors with glucose as the substrate.
Keywords: Microbial fuel cells; Civil engineering; Nutrient recovery; Anaerobic membrane bioreactor; Phosphorus removal; Wastewater